Concurrent cardiac transthyretin and brain β amyloid accumulation among the older adults: The Hisayama study. (13th August 2021) - Hamasaki, Hideomi; Shijo, Masahiro; Nakamura, Ayaka; Honda, Hiroyuki; Yamada, Yuichi; Oda, Yoshinao; Ohara, Tomoyuki; Ninomiya, Toshiharu; Iwaki, Toru
Abstract: Previous studies have revealed risk for cognitive impairment in cardiovascular diseases. We investigated the relationship between degenerative changes of the brain and heart, with reference to Alzheimer's disease (AD) pathologies, cardiac transthyretin amyloid (ATTR) deposition, and cardiac fibrosis. A total of 240 consecutive autopsy cases of a Japanese population‐based study were examined. β amyloid (Aβ) of senile plaques, phosphorylated tau protein of neurofibrillary tangles, and ATTR in the hearts were immunohistochemically detected and graded according to the NIH‐AA guideline for AD pathology and as Tanskanen reported, respectively. Cerebral amyloid angiopathy (CAA) was graded according to the Vonsattel scale. Cardiac fibrosis was detected by picrosirius red staining, followed by image analysis. Cardiac ATTR deposition occurred after age 75 years and increased in an age‐dependent manner. ATTR deposition was more common, and of higher grades, in the dementia cases. We subdivided the cases into two age groups: ≤90 years old (n = 173) and >90 years old (n = 67), which was the mean and median age at death of the AD cases. When adjusted for age and sex, TTR deposition grades correlated with Aβ phase score (A2–3), the Consortium to Establish a Registry for AD score (sparse to frequent), and high Braak stage (V–VI) only in those aged ≤90 years at death. No significant correlation was observed between the cardiac ATTR deposition and CAA stages, or between cardiac fibrosis and AD pathologies. Collectively, AD brain pathology correlated with cardiac TTR deposition among the older adults ≤90 years. Abstract : Pathological specimens obtained from 240 consecutive autopsies showed that cardiac transthyretin (TTR) deposition was observed in participants older than 75 years at death. Severe cardiac TTR deposition was observed more frequently with higher Aβ phase scores, Braak NFT stages, and CERAD scores, but significant correlations were only found in the participants under 90 years at death. Correlation between the cardiac fibrosis and brain amyloid β was not significant.